Sexual rights violations during the conflicts in the Democratic Republic of the Congo between 2005 and 2015 - Wa Baya, Mutombo Joseph (University of the Western Cape, 2019)
Magister Legum - LLM === This thesis examines the sexual rights violation in Eastern DRC, which has been described as the worst in the world. The sexual violence against women and children in this country is systematic and widespread and perpetrated by armed groups, and increasingly also by civilians. The prosecution of sexual offences should contribute to the reduction of these offences, but the Congolese state prosecutes very few cases. The resulting impunity became an obstacle to the state to stop sexual violence, which become unable to overcome the obstacles to prosecutorial action. The successful prosecution of sexual offenders in Eastern DRC faces many obstacles and requires an exceptional jurisdiction which must provide a minimum of better freely conditions to the prosecutors and better unrestrained justice access to the victims. The enforcement of the international instruments of justice will be possible only by this jurisdiction. The victims of sexual violence need more confidence in the jurisdiction which is really working for them to attain justice.